ASSESSMENT OF WOMEN PARTICIPATION IN ENVIRONMENTAL PROTECTION FOR SUSTAINABLE POVERTY REDUCTION IN KURA LOCAL GOVERNMENT AREA, KANO STATE-NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
This study assesses the role of women in environmental protection in Kura local government area of Kano State for sustainable poverty reduction. Both primary and secondary sources of data were used for this study Simple descriptive statistics and the Logistic model was employed in the analysis. The study concludes that women are actively participating in environmental protection and as well play significant role in welfare status of their family. Also the results shows that only the dwelling pattern, the nature of the drainage networks and the source of water are positive and statistically significant to the incidence of poverty among women in the study area, while the kitchen pattern, the bathroom pattern, and the source of fuel for cooking are negative. The results obtained shows that the lack of access to safe water appears more serious as they have to struggle daily to obtain water for their use. The study recommended that, there is need for the government and Non-governmental organization to engage more women in environmental protection because of their role of resource managers. There is the need to address the housing conditions of the women, most especially the dwelling pattern and the nature of dwelling. To improve the well-being of women in the study area adequate provision of infrastructure facilities most especially provision of agricultural products and special awareness by implementing of programmes that will educate women on special nutritional food that should be taken
Keywords: Women, Poverty, Environmental Protection and Sustainable development